Helsinki in Early Twentieth-Century Literature: Urban Experiences in Finnish Prose Fiction 1890-1940 - Ameel, Lieven (Studia Fennica Litteraria, 2014)
"Helsinki in Early Twentieth-Century Literature analyses experiences of the Finnish capital in prose fiction published in Finnish in the period 1890- 1940. It examines the relationships that are formed between Helsinki and fictional characters, focusing, especially, on the way in which urban public space is experienced. Particular attention is given to the description of movement through urban space. The primary material consists of a selection of more than sixty novels, collections of short stories and individual short stories. This study draws on two sets of theoretical frameworks: on the one hand, the expanding field of literary studies of the city, and on the other hand, concepts provided by humanistic and critical geography, as well as by urban studies. This study is the first monograph to examine Helsinki in literature written in Finnish. It shows that rich descriptions of urban life have formed an integral part of Finnish literature from the late nineteenth century onward. Around the turn of the twentieth century, literary Helsinki was approached from a variety of generic and thematic perspectives which were in close dialogue with international contemporary traditions and age-old images of the city, and defined by events typical of Helsinki's own history. Helsinki literature of the 1920s and 1930s further developed the defining traits that took form around the turn of the century, adding a number of new thematic and stylistic nuances. The city experience was increasingly aestheticized and internalized. As the centre of the city became less prominent in literature, the margins of the city and specific socially defined neighbourhoods gained in importance. Many of the central characteristics of how Helsinki is experienced in the literature published during this period remain part of the ongoing discourse on literary Helsinki: Helsinki as a city of leisure and light, inviting dreamy wanderings; the experience of a city divided along the fault lines of gender, class and language; the city as a disorientating and paralyzing cesspit of vice; the city as an imago mundi, symbolic of the body politic; the city of everyday and often very mundane experiences, and the city that invites a profound sense of attachment - an environment onto which characters project their innermost sentiments."